The Fund Agreement in the Courts, Vol. II - Gold, Joseph (International Monetary Fund, 1982)
Written by Joseph Gold, former General Counsel and now Senior Consultant at the IMF, these volumes contain discussions of the ever-increasing body of cases in which the Articles have had a bearing on issues before the courts.